1968
DOI: 10.2136/sssaj1968.03615995003200010025x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Trends and Variability Across Selected Landscapes in Iowa

Abstract: Soil profile features such as A horizon thickness, depth to subsoil mottles, depth to carbonates, and surface and subsoil pH were measured in sample grids on small loess and drift landscape segments. Trend analyses were made across the full range of topography, then soil variation was examined within topographic subareas that approximated detailed soil survey delineations. Comparison of standard errors and standard deviations showed that some increase in the precision of predictions was obtained for loess soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Since B strongly controls the SOC stock, SOC also increases in a similar manner in our model. The findings of our model are also consistent with other studies that found that A‐horizon thickness increases with curvature (Walker et al., 1968a, 1968b). Because C represents how dramatically SOC decays with depth, C is inversely correlated to the A‐horizon thickness.…”
Section: Discussionsupporting
confidence: 93%
“…Since B strongly controls the SOC stock, SOC also increases in a similar manner in our model. The findings of our model are also consistent with other studies that found that A‐horizon thickness increases with curvature (Walker et al., 1968a, 1968b). Because C represents how dramatically SOC decays with depth, C is inversely correlated to the A‐horizon thickness.…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, soil developed operates in three-dimensions within a framework dictated in large measure by the drainage network. The term soil landscape, sometimes shortened to soilscape (Walker et al 1968), captures the three-dimensional nature of the soil body, while the idea of soil–landscape systems (Huggett 1975) emphasizes the dynamic links between soilscapes and other Earth systems. In short, soil is more than a three-dimensional veneer: it is an interdependent body linked to the other terrestrial spheres; or as Wysocki and his colleagues (2011) put it, ‘soils, landscapes, and surficial sediments or rocks together form 3D systems that coevolve through the interaction and balance of physical and chemical weathering versus erosion and deposition.’…”
Section: Topopedologymentioning
confidence: 99%
“…Most previous studies to determine variability in soil constituents have been related to agronomic or taxonomic problems (Beckett, 1967;Beckett and Web ster, 1971;Crosson and Protz, 1974;Drees and Wilding, 1973;Jansen and Arnold, 1976;McCormack and Wild ing, 1969;McKenzie, 1955;Oertel, 1959;Protz, Presant, and Arnold, 1968;Reynolds, 1975;Walker, Hall, and Protz, 1968;Webster and Butler, 1976;and Wilding, Jones, and Schafer, 1965). These studies considered dif ferent soil properties at different geographic scales from those considered in this study.…”
Section: Introductionmentioning
confidence: 99%